Temporal Dynamics and the Contribution of Plant Organs in a Phenotypically Diverse Population of High-Yielding Winter Wheat: Evaluating Concepts for Disentangling Yield Formation and Nitrogen Use Efficiency - Prey, Lukas; Hu, Yuncai; Schmidhalter, Urs (Frontiers in Plant Science, 2019)
Enhancing crop nitrogen use efficiency (NUE) is a key requirement for both economic and ecological reasons. Consequently, the genotypic potential for NUE in winter wheat (Triticum aestivum L.) requires further exploitation. Emerging plant phenomic techniques may provide knowledge about traits contributing to grain N uptake (GNup) and grain yield (GY). However, the understanding of beneficial strategies concerning the temporal dynamics of NUE and grain yield formation and the role of plant organs is still scarce especially under high-yielding European conditions – particularly to discriminate interesting lines in the breeding process. Thus, screening for potentially useful NUE traits in terms of variation, stability and contribution to target traits will be an essential prerequisite for the development of efficient phenotyping strategies. Therefore, forty-six NUE and yield formation traits were assessed in a population of 75 breeding lines over three years from 2015 to 2017 in southern Germany, including dry matter (DM), N concentration and N uptake at anthesis and maturity, both at the aboveground-plant and plant organ levels. Significant genotype and genotype*environment effects were observed for all traits. While GY was more related to post-anthesis assimilation, also DM translocation contributed substantially to GY by 31-44%. At maturity, total aboveground DM as opposed to harvest index predominantly determined GY. NUE for GY was better described by N uptake efficiency than by N utilization efficiency. GNup was greatly influenced by variation in GY, but not in grain N concentration, and by total N uptake and not the N harvest index. Post-anthesis N uptake highly depended on the year and was low in comparison to N translocation. However, post-anthesis N uptake was always correlated with GNup, suggesting the need to also consider stay-green strategies under temperate growing conditions. While anthesis traits were only moderately descriptive, GY will be enhanced by increasing total biomass and the N uptake efficiency. Similarly, targeting total N uptake, particularly at post-anthesis, seems to be a rewarding strategy to boost GNup. Thus, high-throughput phenotyping should be targeted rather towards detecting traits related to DM and Nup acquisition than to the internal allocation and rather to post-anthesis than to anthesis traits.